Improving the postpartum care of women with a recent history of preeclampsia: a focus group study. (2nd July 2016) - Skurnik, Geraldine; Roche, Andrea Teresa; Stuart, Jennifer J.; Rich-Edwards, Janet; Tsigas, Eleni; Levkoff, Sue E.; Seely, Ellen W.
ABSTRACT: Objective : Women with prior preeclampsia are at increased risk of cardiovascular disease (CVD). This study investigated barriers and facilitators toward learning about this link and engaging in lifestyle modifications to reduce this risk. Methods : Four focus groups were held with 14 women within 6 months of a preeclamptic pregnancy. Results : Participants were unaware of the link between preeclampsia and CVD, suggested improvements to provider–patient communication, and discussed the benefits of social support and online tracking (weight, blood pressure) in making lifestyle modifications. Conclusions : Solutions offered may improve efforts to modify lifestyle and communication between providers and women about this link.